Revising Lehár's Rastelbinder for the Reich. (10th July 2014) - Petersen, Ulrike
Abstract: Operetta held an ambiguous position within Nazi German entertainment culture: while suitably diverting and escapist, many of the most successful hits had Jewish authors and were thus increasingly avoided by theatre directors. To replenish the Reich's performable repertory, Goebbels founded the 'Reichsstelle für Musikbearbeitungen', whose revisions of classical works including Handel's oratorios and Mozart's Da Ponte operas have been widely discussed. This article focuses on one of the institution's many operetta commissions, Viennese satirist Rudolf Weys's unfinished 1944 version of Franz Lehár's Der Rastelbinder (1902), a box office success that featured an itinerant Jewish peddler as the central character. Weys's revisions as well as his own story show that this kind of Reichsstelle commission could be a lifeline for artists who could not afford to attract attention or leave the Reich.